The effects of maternal body mass index (BMI) on the pregnancy outcome among primigravida who delivered at Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang - Mohamed@Mohd Adnan, Siti Anisah; Ismail, Hamizah; Mohd Rus, Razman; Nusee, Zalina (Elsevier Ireland Ltd., 2012)
Objective: To measure the prevalence of maternal and fetus/ newborn complications during antenatal, intrapartum and postpartum periods and the intrapregnancy weight gain for each BMI category. Methods: This is a cohort study between December 2011 and November 2012. The study includes all primigravida who booked before 14 weeks of gestation. Upon delivery women had their antenatal, intrapartum and postpartum events reviewed and then categorized into five BMI groups; underweight (£19.9 kg/m2), normal (20–24.9 kg/m2), overweight (25–29.9 kg/m2), obese (30– 34.9 kg/m2) and morbidly obese (>35 kg/m2). Women were followed up until discharged and reviewed again at 6 weeks postpartum. All statistical analyses were performed with the use of SPSS for Windows, version 18.0 (SPSS) and P value of <0.05 was taken to be statistical significant. Results: A total of 102 women were enrolled. There were 29 (28.4%) underweight, 36 (35.2%) normal weight, 14 (13.7%) overweight, 19 (18.6%) obese and 3 (2.9%) morbidly obese women. The mean age was 26 years (SD 4.0) and the majorities were Malays (90.2%). The morbidly obese group was found to experience higher percentage of gestational diabetes mellitus (33%), pregnancy induced hypertension (100%), preterm delivery (33%), augmentation (100%) and instrumentation (33%). Risk of caesarean section was highest (64%) in the overweight group. Highest risk of shoulder dystocia (33%) and wound dehiscence (15.8%) were observed in the obese group. The underweight women had higher risk for preterm delivery (17%). The mean intrapregnancy weight gain for each BMI category were:12.2 ± 4.6 kg (underweight), 13.6 ± 4.4 kg (normal), 12.8 ± 5.5 kg (overweight), 12.4 ± 6.2 kg (obese) and 0.8 ± 7.8 kg (morbidly obese). Morbidly obese group had lower intrapregnancy weight gain compared to other groups (P = 0.004). Conclusion: The maternal risk increases as the BMI increases whereas the fetal risk increases with the extreme of BMI (underweight and morbidly obese). Inappropriate weight gain was observed in all groups but was significant in the morbidly obese.